The elderly inflammatory bowel disease patient and osteoporosis. (February 2012) - Katz, Seymour; Weinerman, Stuart
Inflammatory bowel disease increases the risk of osteoporosis by multiple mechanisms. The risk of osteoporosis-related fractures weighs heavily on the elderly inflammatory bowel disease population, due to the combination of aging and menopause on the underlying disease-associated risk. Risk factors are reviewed, as well as pathophysiologic mechanisms including inflammation, malabsorption and nutritional deficiencies, and use of glucocorticoid therapy. New data concerning vitamin D and the inflammatory disease is highlighted. Current recommendations concerning screening for bone disease in inflammatory bowel disease patients are reviewed. Therapy with vitamin D, calcium and bone-specific agents such as bisphosphonates, hormone replacement therapy, calcitonin and teriparatide are discussed, as well as potential benefits of direct treatment of the inflammation.